The impact of economic interdependence on the probability of conflict between states: The case of "American-Chinese relationship on Taiwan since 1995" - Mina E. Tanious (Review of Economics and Political Science (REPS), 2019)
Purpose - The purpose of this paper is to explore to what extent the economic interdependence can affect the likelihood of conflict between States. Specially, over the past few decades, there has been a huge interest in the relationship between economic interdependence and political conflict. Liberals argue that economic interdependence lowers the possibility of war by increasing the weight of trading over the alternative of aggression; interdependent states would rather trade than invade; realists dismiss the liberal argument, arguing that high interdependence increases rather than decreases the probability of war. In anarchy, states must constantly worry about their security. Design/methodology/approach - This paper highlights the content and level of economic interdependence between China and the USA since the beginning of China's economic reform in 1979 and examines the impact of economic interdependence between them on their relationship toward Taiwan since 1995 and the probability of conflict. Findings - Economic interdependence is proved to significantly decrease the onset of conflict between the two parties. This can be shown by comparing the number of armed conflicts during the pre-interdependence period to the number of armed conflicts after the economic interdependence there was an overage of 0.79 militarized interstate disputes (MIDs)/year, compared to 0.26 MIDs/year following China's economic reforms; also, the length of the hostilities was longer during the pre-interdependence period (with an average of 11.13 months versus 5.33 months). Originality/Value - This means that economic interdependence does not completely prevent the outbreak of international conflicts, but it also plays a major role in influencing the conflict in terms of the conflict's intensity, the use of armed force and the number of conflicts that occur between the economic interdependence states.
Keywords: 330; Trade; Economic interdependence; International conflict; Militarized interstate dispute